Website Development and Management Training as Information Publication Media in Tambong Village Banyuwangi - Agus Priyo Utomo; Lukman Hakim; Ruth Ema Febrita (Poltanesa, 2023)
Tambong Village is a regional unit in Banyuwangi Regency, which was currently a priority for the government to develop because it has potential that needs to be explored and developed to improve its citizens' welfare. Likewise, the development of human resources in rural areas should be prioritized so that regional competitiveness increases. One of the things that can trigger increased competitiveness between villages is to utilize information technology to provide information to residents and the broader community about what is in the village (for example, tourist attractions). For this reason, a website page is needed to convey information, and this page can also be used to report activities or other information to increase community enthusiasm to participate in the activities carried out. However, the village website page that has been provided has yet to be filled in with a content management system, so it cannot display information on activities and tourist attractions in Tambong village. It is because the village officials in charge of managing the village website still need more knowledge about the technical management of the information on the website. In addition, village officials also need knowledge and skills so that the information conveyed on the website can be packaged in an informative manner. Based on the needs of Tambong Village officials, this community service activity will train village officials on how to manage the website and use the Google Maps application so that the village website can be continuously updated and maximized to display quality information to the community and become information media to attract tourists to Tambong Village tourist attractions. After undergoing training, village officers were assigned to create website content, and villagers were asked to assess the quality of the content through a survey. The survey consisted of 9 questions and was conducted on 20 village residents. The survey results showed that the quality of the content created by the village officers was already good.